Rice yield in Costa Rican Central Pacific did not improve with a urease inhibitor - Pérez Castillo, Ana Gabriela (2024)
Urea is widely used as nitrogen (N) source for rice fertilization in Costa Rica, despite its low efficiency 15 linked to ammonia losses. To assess urea management alternatives, two field experiments were 16 conducted in the Central Pacific region of Costa Rica to study the effect of N-(n-butyl) thiophosphoric 17 triamide (NBPT) on rice yield and N use efficiency (NUE). In Experiment 1 (Exp1) three tillage 18 treatments (commercial-CT-, reduced-RT-, and reduced tillage with previous subsoiler-RTS-) were 19 evaluated with three N managements: control (without N), urea at 124 kg N ha-1 with and without 20 NBPT. In Experiment 2 (Exp2), a 100 kg N ha-1 dose (with and without NPBT) was evaluated along 21 with a control (without N). NUE was estimated using 15N urea isotopic labeling technique for both 22 trials. In Exp1, a significant difference of 4.8% in NUE for grain was observed among urea with and 23 without NBPT, but no tillage effect was observed. No statistically significant differences were 24 observed in yield among the fertilization treatments (Exp1: 3.56 ± 0.98 t ha-1 for urea and 3.85 ± 0.85 25 t ha-1 for urea with NBPT; Exp2: 3.38 ± 0.39 t ha-1 for urea and 3.40 ± 0.58 t ha-1 for urea with NBPT) 26 or due to different tillage practices (CT: 3.33 ± 0.79 t ha-1, RT: 3.56 ± 0.74 t ha-1, and RTS: 4.23 ± 0.98 27 t ha-1). Although the NBPT is a viable option to reduce ammonia losses, its adoption in tropical 28 conditions might be restricted by the small impact on yield.